Dramatic decline in new HIV diagnoses in persons born in France in a large nationwide HIV cohort. (July 2021) - Le Guillou, A.; Cabie, A.; Delpierre, C.; Pugliese, P.; Jacomet, C.; Hentzien, M.; Duvivier, C.; Zaegel-Faucher, O.; Cotte, L.; Raffi, F.; Bani-Sadr, F.; ,
Abstract: Objectives: As trends in new HIV diagnoses represent a measure of the HIV epidemic, we conducted a 6-year longitudinal study to evaluate the change in rates of new HIV diagnosis, stratified by birthplace, HIV risk groups and CD4 cell count at diagnosis in a large French multicentre cohort. Study design: We performed a retrospective cohort study using data from the mainland French Dat'AIDS cohort. Methods: Data were obtained for subjects with a new HIV diagnosis date between 2013 and 2018. HIV diagnosis date was defined as the date of the first known positive HIV serology. Results: Between 2013 and 2018, a total of 68, 376 people living with HIV (PLHIV) were followed in the Dat'AIDS cohort; 9543 persons were newly diagnosed with HIV. The annual number of new HIV diagnoses decreased from 1856 in 2013, to 1149 in 2018 (−38.1%), P = 0.01; it was more pronounced among subjects born in France, from 858 to 484 (−43.6%), P < 0.01, than in those born abroad (−23.8%, from 821 to 626, P = 0.13). Among subjects born in France, the decrease over the period was −46.7% among men who have sex with men (MSM), −43.5% for heterosexual women and −33.3% for heterosexual men. Conclusion: Our findings show changes in HIV epidemiology in PLHIV born in France, with a decline around 40% in new HIV diagnoses, and a more pronounced decrease among MSM and heterosexual women. Our results support the long-term effectiveness of the antiretroviral therapy as a prevention strategy among the various tools for HIV prevention.